Impaired male sex development in an infant with molecularly defined partial 9p monosomy: implication for a testis forming gene(s) on 9p. Issue 4 (April 1997) - Ogata, T; Muroya, K; Matsuo, N; Hata, J; Fukushima, Y; Suzuki, Y
Abstract : This paper describes a genetically male infant with impaired male sex development and partial 9p monosomy. The external genitalia were ambiguous with microphallus (penile length at birth 10 mm, mean age matched normal length 29 mm (SD 5)), hypospadias, and hypoplastic scrotum. The tests were undescended and severely hypoplastic (testis size at 12 months of age, right 8 x 5 x 4 mm and left 4 x 3 x 2 mm; mean age matched normal size, length 18 mm (SD 2), width 11 mm (SD 1). Cytogenetic studies showed a 46, XY, del(9)(p23) karyotype in all the 30 peripheral lymphocytes and 20 skin fibroblasts examined. Microsatellite analysis for a total of 13 loci assigned to the 9p22-24 region showed that the deleted chromosome 9 was of paternal origin and was missing a region distal to D9S168. Southern blot analysis for D9S47 also confirmed the 9p deletion. The sequence of SRY was normal. The results provide further support for the previously proposed hypothesis that a gene(s) for testis formation is present on the distal part of 9p and indicate in molecular terms that the putative testis forming gene(s) resides in the region distal to D9S168.